The wall [videorecording (DVD)] - Kinsella, David, 1964-; McKinley, Corey; Shin, Yuna (Dreamscape Media, LLC, 2018)
Told through a mix of live action and animation, this is the story of Yung Hee, a young female poet living under North Korea's regime.